2006
DOI: 10.1002/chin.200638224
|View full text |Cite
|
Sign up to set email alerts
|

The Chemistry of Disilyne with a Genuine Si—Si Triple Bond: Synthesis, Structure, and Reactivity

Abstract: In this account, our recent results on the chemistry of a stable silicon-silicon triply-bonded compound, disilyne, including recent advances in the chemistry of stable alkyne analogues of heavier group 14 elements, are described. Our original extremely bulky trialkylsilyl substituent, Dis 2 i PrSi [Dis = CH(SiMe 3 ) 2 ], has enabled the isolation of disilyne as a stable compound, which has been completely characterized by various spectroscopic techniques, as well as X-ray crystallography. Some reactivity of ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…15 The disilyne 2 also exhibits a trans-bent structure with bending angles of 138.78(5)°for the Dsi 2 i PrSi side and 137.89(5)°for the Dsi 2 NpSi side. The SitSi bond length of 2 (2.0569(12) Å) is remarkably shorter than typical SidSi bond lengths (2.143-2.228 Å), 18 demonstrating its triple-bond character, and is also shorter than those of 1a (2.0622(9) Å) 10 and BbtsSitSisBbt (2.108(5) Å). 13 In the 29 Si NMR spectrum of 2 in C 6 D 6 , eight signals are observed at -3.5, -0.5, -0.3, 0.0, 0.1, 22.1, 62.6, and 106.3 ppm, the former six signals being due to the silicon atoms of the substituents.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…15 The disilyne 2 also exhibits a trans-bent structure with bending angles of 138.78(5)°for the Dsi 2 i PrSi side and 137.89(5)°for the Dsi 2 NpSi side. The SitSi bond length of 2 (2.0569(12) Å) is remarkably shorter than typical SidSi bond lengths (2.143-2.228 Å), 18 demonstrating its triple-bond character, and is also shorter than those of 1a (2.0622(9) Å) 10 and BbtsSitSisBbt (2.108(5) Å). 13 In the 29 Si NMR spectrum of 2 in C 6 D 6 , eight signals are observed at -3.5, -0.5, -0.3, 0.0, 0.1, 22.1, 62.6, and 106.3 ppm, the former six signals being due to the silicon atoms of the substituents.…”
mentioning
confidence: 93%
“…15 The silicon-silicon triple bonds of all reported disilynes are trans-bent, not linear, which results in two nondegenerate occupied π-MOs (π in as the HOMO -1 and π out as the HOMO) and two unoccupied antibonding π*-MOs (π* in as the LUMO and π* out as the LUMO + 1). 10 The molecular structure of disilyne 2 as determined by X-ray crystallographic analysis is shown in Figure 1. 15 The disilyne 2 also exhibits a trans-bent structure with bending angles of 138.78(5)°for the Dsi 2 i PrSi side and 137.89(5)°for the Dsi 2 NpSi side.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In essence the structure of the di-A C H T U N G T R E N N U N G stannene demonstrated that the familiar valence-bond model used for multiple bonding in alkenes and alkynes was insufficient to deal with the structural changes observed in their heavier-element analogues. Numerous examples of heavier group 14 element alkene analogues, [3] most notably the landmark disilenes, [4,5] and more recently a complete series of alkyne congeners [6][7][8][9][10] has been synthesized and characterized. Currently it is broadly accepted (although controversies continue to arise) that the structural differences seen in the heavier element derivatives are a manifestation weakened bonding and an increasing preference for lone pair character over p-bonding as the group is descended.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Tokitoh et al also reported a diaryldisilyne by using Bbt substituents (Bbt ) 2,6-bis[bis(trimethylsilyl)methyl]-4-[tris(trimethylsilyl)methyl]phenyl). 7 Since our report on disilyne 1 in 2004, 5 we have also investigated the reactivity of 1 toward alkenes, 8 alkynes, 8 t BuLi, 9 alkali metals, 9,10 and silyl cyanide, 11 to understand the nature of the π bonds of the triple bond. 12 Among them, we found that the reaction of 1 with trimethylsilyl cyanide unexpectedly produced two types of products: the 1:2 adduct with bis(silaketenimine) character and the 1,4-diaza-2,3-disilabenzene analogue, in which two isomers of trimethylsilyl cyanide, the isocyanide and cyanide forms, compete to react with 1.…”
mentioning
confidence: 99%